Changes in some macro and micronutrient status in relation to pre-puddling tillage and puddling intensity in different soils cropped with rice (Oryza sativa) - SIDHU, A S; KUKAL, S S; DIWEDI, B S; SINGH, DALEL; THIND, SS; SINGH, V K (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during 2000-2003 to study the interactive effects of puddling and pre-puddling tillage operations on changes in nutrient status and rice yield in sandy loam soils of Ludhiana (Punjab) and Modipuram (Uttar Pradesh) and silty clay 10aln soil of Kaul (Haryana). The treatments included 3 levels of pre-puddling tillage, viz I (PP\), 2 (PP2) and 4 (PP4) passes of tractor-drawn cultivator followed by 1 planking each in the main plots and 3 levels of puddling, viz 1(P 1), 2 (P2) and 4 (P4) passes oftractor-drawn cultivator in standing water, in the sub-plots of all the soils. Increasing puddling intensity helped retain more nlineral-Nin profile by reducing the N leaching losses. The effect of puddling intensity for retaining higher amount of available N in profile was more pronounced at PP1 level of pre-puddling tillage while in PP2 and PP4 levels, the increase in available N retention in profile was observed only up to P2 level of puddling. The available K content of soil decreased with increase in puddling intensity in all the soils. Increased puddling intensity decreased the amount of Zn in sandy loam soil (Ludhiana) but increased the amount of Fe and Mn whereas cu remained unaffected.